AUTOMATED MODEL GENERATION OF FSM AND NUSMV MODEL FROM RSA JAVA SOURCE CODE FOR MODEL CHECKING - SALLEH AL-HUMAIKANI, MOHAMMED ABDULQAWI (2021)
The encryption algorithms are playing an important part in the protection level for data. RSA is one of these encryption algorithms that have been implemented in security systems. Security systems are built by developing their source codes with different programming languages such as Java language. Therefore, there is always possibility of mistakes that can be found when performing the RSA algorithm in the source code. However, model checking is one of the approaches that help to discover these fault.